"Protective Mimicry": Forster's Literary Imitation of 'Divide and Rule' in A Passage to India - Zeenat, Afrin (EAST WEST JOURNAL OF HUMANITIES, 2010)
Critical response to E. M. Forster's A Passage to India remains diverse. While some commend Forster's depiction of the India, others express their misgivings at his portrayal of Indians attributing his delineation of the Indians, their behaviors, their religions and customs, even the geographical landscape to be in the Orientalist tradition. While looking at the historical bases of A Passage to India, this paper establishes that being conscious of the British administration's policy of 'divide and rule,' Forster undertakes a similar exercise of widening the gulf between the Hindus and Muslims. Forster's 'knowledge' of the political conditions in India and Europe, the differences between the two communities and his imperial anxieties pertaining to the future of the British Empire shapes his representation of Hindus and Muslims as two distinct 'types,' as a form of literary mimicry of the British policy of 'divide and rule.' This paper also argues that A Passage to India's importance as a seminal colonial text in India has helped reinforce this difference in the Indian consciousness and continues to foment communal riots in the country even ninety years after its publication